Trends in the Division of Matrimonial Property Based on Contribution: an Empirical Case Study Based on the Structured Approach in Singapore. (16th May 2022) - Chan, Leon Vincent; Xu, Kaizhe Richard
Abstract: Different jurisdictions have adopted different approaches to the division of matrimonial property. While some have greater certainty and predictability from a rules-based approach that adopts equal division as a starting point, others have adopted a discretionary approach with little to no guidance from the legislation. Using statistical methods, this empirical quantitative study seeks to show how trends (and in turn certainty and predictability) can be obtained from a discretionary system, using Singapore's contributions-based approach as a case study. Analysing 265 Singaporean judgements, the authors observed, amongst other trends, that division for both single-income and dual-income marriage tend to incline towards equality as the marriage length increases; there are divergences in collective outcomes from the Singapore Court of Appeal and Singapore High Court, and judgements from the Singapore Family Justice Courts; direct contributions have a significant impact on division for dual-income marriages; and the presence of child(ren) significantly influences division.